Design Chart of Trough Width Value for Rectangular Shaped Tunnel - Mohd Nasir, Muhammad Yusoff; Mohamad, Hisham; Ghazali, Muhammad Farid; Ahmran, Muhammad Shafiq Aiman (International Journal of Integrated Engineering, 2024)
The rectangular tunnel has proven as the best technique for depth clearance and utilizing the space of cross-section compared with the circular tunnel. In designing the rectangular tunnel, trough width parameters found from the literature mostly were designed for circular shape tunnels only. The main objective of this paper is to develop a design chart of trough width value for rectangular tunnels through a parametric study comprising a variation of tunnel size ratios using numerical analyses. PLAXIS 2D, a finite element modelling software, was used to generate rectangular tunnel models with shield support under different conditions. Developing a design chart could increase the intention of constructing a rectangular-shaped tunnel for tunnel engineers and increase the impact on green engineering. Design charts for rectangular tunnels held at depths of 4 m, 5 m and 6 m were developed and validated with field data from the literature for the potential application of trough width value that matches clayey ground conditions. Soft soil conditions may not be applicable to be applied on these charts.